Penggunaan Indole Butirat Acid (IBA) untuk Induksi Akar Setek Amorphophallus titanum dan Amorphophallus gigas - Setiawan, Ryan Budi; Yusniwati; Handayani, Mellyyana; Jumsalia (Jurnal Hortikultura Indonesia, 2023)
Amorphophallus titanum and Amorphophallus gigas are endemic flora of Sumatera that are threatened with extinction. Plant propagation by cuttings can be used to support plant conservation. The success of cuttings is determined by the concentration of plant growth regulators (PGR) required to stimulate root, corms and shoot formation. Therefore, study about PGR concentrations is crucial for research. This study aimed to obtain the best concentration of IBA to induce roots and corms in A. titanum and A. gigas. The study was conducted from July-October 2022. The study was arranged based on a completely randomized design with IBA concentration treatment consisting of 5 levels: 5, 10, 15, 20, and 25 mg L-1. Cuttings in A. titanum use rachis and petiole, whereas in A. gigas only use rachis. The results showed that petiole cuttings showed a better response than rachis in inducing root formation. IBA concentration of 15 mg L-1 resulted in a rooting percentage of 80% in petiole cutting of A. titanum and 20% in rachis cutting of A. gigas. Keywords: biodiversity, conservation, endemic, extinct, plant growth regulator